Health Insurance Status and the Care of Nursing Home Residents with Advanced Dementia - Goldfeld, Keith S. (2013)
IMPORTANCE: Nursing home residents with advanced dementia commonly experience burdensome and costly hospitalizations that may not extend survival or improve the quality of life. Fragmentation in health care has contributed to poor coordination of care for acutely ill nursing home residents. OBJECTIVE: To compare patterns of care and quality outcomes for nursing home residents with advanced dementia covered by managed care to those covered by traditional fee-for-service Medicare. DESIGN: The Choices, Attitudes, and Strategies for Care of Advanced Dementia at the End-of-Life (CASCADE) study was a prospective cohort study that followed 323 nursing home residents over eighteen months to better understand the course of advanced dementia at or near the end of life. CASCADE and Medicare data were linked to determine the health insurance status of study participants. SETTING: Twenty-two nursing homes in the Boston area. PARTICIPANTS: Nursing home residents with advanced dementia and their health care proxies. EXPOSURE: The health insurance status of the resident, either managed care or traditional fee-for-service. MAIN OUTCOMES: The outcomes included survival, symptoms related to comfort, treatment of pain and dyspnea, presence of pressure ulcers, presence of a DNH order, treatment for pneumonia, hospital transfer (hospitalization or emergency room visit) for an acute illness, hospice referral, primary care visits, and family satisfaction with care. RESULTS: Residents enrolled in managed care (n=133) were more likely to have do-not-hospitalize orders compared to those in traditional Medicare fee-for service (n=158) (64% vs. 51%, p-value < 0.05), were less likely to be transferred to the hospital for acute illness (4% vs. 16%, p-value < 0.05), had more primary care visits per 90 days (4.8±2.6 vs. 4.2±5.0, p-value < 0.05), and had more nurse practitioner visits (3.0±2.1 vs. 0.8±2.6, p-value < 0.05). Survival, comfort, and other treatment outcomes did not differ across groups. CONCLUSIONS AND RELEVANCE: Medicare managed care programs may offer a promising approach to ensure that nursing homes are able to provide appropriate, less burdensome and affordable care, especially at the end-of-life.